IMPROVING STUDENTS’ VOCABULARY THROUGH DISPLAY TABLE GAME - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this research is to prove whether display table games are effective or not in improving students’ vocabulary at SMP Negeri 1 Ratahan. This study is quantitative, with a pre-experimental design and a one-group pretest and post-test design. An objective test was used to collect data for this study. The findings of this study revealed that students' post-test scores were higher than their pre-test scores. The mean of the post-test was 73, while the mean of the pre-test was 61.5. It means that using display table games in teaching vocabulary is effective in increasing students’ vocabulary.